Petrography of the Amphibolites of Swat and Kohistan - Jan, M. Qasim (Journal of Himalayan Earth Sciences, 1979)
The amphibolites of Swat and Kohistan are mainly found in two belts. Those forming the southern belt are the prograde metamorphic products of basic to intermediate rocks which were intruded into tuffs, with some volcanic fiows; the tuffs now represented by banded amphibolites. The rocks are locally migmatitic and are essentially composed of hornblende, plagioclase and/or olinoepidote, with garnet and/or quartz in some places. Opaque minerals, rutile and/or sphene are the common accessory minerals, whilst white and dark micas, plinopyroxene, carbonate, K-feldspar, margarite, corundum, cummingtonite, zoisite, green spinel and staurolite are locally present. The amphibolites of the granulite belt are retrograde products of the pyroxene granulites, mainly due to an influx of water, and are essentially composed of hornblende and plagioclase.